The association between shallow vestibular depth and peri-implant parameters: a retrospective 6 years longitudinal study - Halperin-Sternfeld, Michal; Zigdon-Giladi, Hadar; Machtei, Eli E. (Journal of clinical periodontology, 2016)
Aim The aim of this study was to retrospectively evaluate the association between shallow vestibular depth (VD) and peri‐implant parameters. Material and Methods Peri‐implant parameters were evaluated in 61 periodontal patients under regular supportive periodontal therapy. Clinical parameters included gingival index (GI), plaque index (PI), bleeding on probing (BOP), peri‐implant pocket depths (PPD), mucosal recession (MR), relative attachment level (RAL), width and thickness of keratinized mucosa (KMW, KMT) and VD. Radiographic bone level (RBL) was measured on peri‐apical radiographs. Results Sites with shallow VD (≤4 mm) were associated with higher MR (0.91 mm versus 0.47 mm, p ≤ 0.009), higher RAL (4.23 mm versus 3.59 mm, p ≤ 0.0001) and higher RBL (2.18 mm versus 1.7 mm, p = 0.05) when compared with adequate vestibular depth sites (VD >4 mm). Moreover, sites with shallow VD presented lower KMW compared with sites with adequate VD (1.24 mm versus 2.38 mm, respectively, p ≤ 0.0001). Slightly greater BOP, and GI were recorded for the shallow VD compared with adequate sites. According to multivariate analysis, factors that could predict RAL included: VD, GI, age, supporting periodontal therapy, implant type and design. Conclusions Based on this study, inadequate vestibular depth around dental implants may be associated with increased peri‐implant bone loss and mucosal recession. Further prospective and intervention studies will be required to fully understand this phenomenon.